2019
DOI: 10.1111/jspn.12231
|View full text |Cite
|
Sign up to set email alerts
|

Sugar‐sweetened beverage behaviors of Tennessee school children: How do parent‐ and child‐report compare on school days and nonschool days?

Abstract: Introduction This study describes sugar‐sweetened beverage (SSB) behaviors of children and compares child‐reported SSB behaviors to parent‐reported SSB behaviors during school days and nonschool days. Method Six elementary schools from Tennessee participated with 444 students and 287 parents. Descriptive statistics included means, standard deviation (SD), ranges of values, and measures of central tendency. To explore the relationship between parent and child report, intraclass correlation coefficients (ICC) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…In Chile, steviol glycosides are the second most used LNCS in the food supply, which has raised concerns that ADI value could be exceeded in some vulnerable groups, such as children ( 16), but a subsequent study indicated that this is not the case (48). A Portuguese study highlighted steviol glycosides as most commonly present in iced teas (41), which are a popular choice for children (49). Therefore, careful monitoring of this is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…In Chile, steviol glycosides are the second most used LNCS in the food supply, which has raised concerns that ADI value could be exceeded in some vulnerable groups, such as children ( 16), but a subsequent study indicated that this is not the case (48). A Portuguese study highlighted steviol glycosides as most commonly present in iced teas (41), which are a popular choice for children (49). Therefore, careful monitoring of this is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding evaluations of health behavior, several studies have investigated agreement for questions of diet, physical activity, media use, or sleep. With respect to children's diet, the amount of parent-child agreement has been shown to differ depending on the type of food assessed, with low agreement for the consumption of fruits and vegetables [5][6][7], but slightly higher agreement for sweetened beverages [7,8], and moderate agreement for the consumption of fish, eggs, and fast food [7]. Regarding aspects of eating culture, e.g., having breakfast or sharing dinners, agreement between child and parent reports has been shown to be low to fair [9].…”
Section: Introductionmentioning
confidence: 99%
“…This study further supports that students can serve as effective health coaches, advocates, leaders, mentors, and role models to individual behavioral change, broader environmental change, and policy changes within schools. The student-designed and student-delivered approach to support the adoption of health lifestyle behavioral change is rooted in evidence-based practice (Petosa & Smith, 2014; Smith & Baumker, 2019; Smith & Holloman, 2014). Adolescents tend to view peers as more credible, having a better understanding of the concerns of young people, and more likely to model the behaviors of peers than adults (Ebberling et al, 2012; Millitello, Kelly, Melnyk, Smith, & Petosa, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of a larger project targeting 11 schools in Tennessee. Findings from a related study focusing on elementary aged children and their parents are published elsewhere (Smith & Baumker, 2019). The purpose of this study was to examine the impact of a high school-based, student-led project aimed at limiting short-term SSB consumption behaviors and increasing daily water consumption behaviors.…”
mentioning
confidence: 99%